(untitled) (American Journal of Business Management, Economics and Banking, 2022)
The first manifestations of marketing activity are attributed to the very beginning of the formation and development of commodity-money relations. Information about the first advertisement of the product is found in the countries of ancient civilization in Sumer, Egypt, in the states of ancient Mesopotamia, Japan [11]. The theoretical foundations of marketing as an independent science existing at the intersection of economics, sociology and management were laid in the XIX century by the American Sares McCormick (1809-1884).